Defining the protein and lipid constituents of tubular recycling endosomes - Farmer, Trey (J Biol Chem, 2021)
Once internalized, receptors reach the sorting endosome and are either targeted for degradation or recycled to the plasma membrane, a process mediated at least in part by tubular recycling endosomes (TREs). TREs may be efficient for sorting owing to the ratio of large surface membrane area to luminal volume; following receptor segregation, TRE fission likely releases receptor-laden tubules and vesicles for recycling. Despite the importance of TRE networks for recycling, these unique structures remain poorly understood, and unresolved questions relate to their lipid and protein composition and biogenesis. Our previous studies have depicted the endocytic protein MICAL-L1 as an essential TRE constituent, and newer studies show a similar localization for the GTP-binding protein Rab10. We demonstrate that TREs are enriched in both phosphatidic acid (PA) and phosphatidylinositol-4,5-bisphosphate (PI(4,5)P2), supporting the idea of MICAL-L1 recruitment by PA and Rab10 recruitment via PI(4,5)P2. Using siRNA knock-down, we demonstrate that Rab10-marked TREs remain prominent in cells upon MICAL-L1 or Syndapin2 depletion. However, depletion of Rab10 or its interaction partner, EHBP1, led to loss of MICAL-L1-marked TREs. We next used phospholipase D inhibitors to decrease PA synthesis, acutely disrupt TREs, and enable monitoring of TRE regeneration after inhibitor washout. Rab10 depletion prevented TRE regeneration, whereas MICAL-L1 knock-down did not. It is surprising that EHBP1 depletion did not affect TRE regeneration under these conditions. Overall, our study supports a primary role for Rab10 and the requirement for PA and PI(4,5)P2 in TRE biogenesis and regeneration, with Rab10 likely linking the sorting endosome to motor proteins and the microtubule network.